Of Flights and Flotillas: Assimilation and Race in the Cuban Diaspora - Woltman, Kelly; Newbold, K. Bruce (The Professional geographer, 2009)
Recent work on the integration of immigrants suggests that the process of assimilating into American society often occurs along fragmented paths. The segmented assimilation theory contends that discrimination and unequal opportunities affect processes of adaptation. This article considers this theory in the context of how the adaptation of Cuban émigrés differs along lines of race. Using data from the 1990 and 2000 U.S. Census 5 percent Public Use Microdata Samples, we investigate the process of assimilation and settlement among the Freedom Flight and Mariel Cuban exiles in Miami. Results suggest that the speed and degree of assimilation differs according to race, subject to nationality and period of arrival.